2003
DOI: 10.1080/1025389031000116479
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery of NK Cell Activity in Mice under Restraint Stress by the Administration of a Biological Response Modifier Derived from the Mycelia of the Basidiomycete Tricholoma matsutake

Abstract: Some types of stressor act on the immune system via the network comprising the endocrine-immune-nervous systems, and are reportedly responsible for the onset of diseases as well as giving impetus to their advance. It is important for the maintenance and promotion of health to cope with stress-induced changes in immunocompetence. Therefore, we studied the effects of administration of a novel biological response modifier (CM6271) derived from the mycelia of the basidiomycete Tricholoma matsutake on the NK cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Our previous experiments showed that CM6271 did not affect the reduction of the splenic NK cell activity in mice treated with a single incidence of 18-hour restraint stress, but CM6271 enhanced recovery after discharge from restraint [15]. The differences between the results obtained under the single restraint stress conditions and the effects on the splenic NK cell activity observed in the present study may have been due to the difference in the restraint stress conditions.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Our previous experiments showed that CM6271 did not affect the reduction of the splenic NK cell activity in mice treated with a single incidence of 18-hour restraint stress, but CM6271 enhanced recovery after discharge from restraint [15]. The differences between the results obtained under the single restraint stress conditions and the effects on the splenic NK cell activity observed in the present study may have been due to the difference in the restraint stress conditions.…”
Section: Discussioncontrasting
confidence: 63%
“…To clarify the usefulness of CM6271, we used an animal model to study the effects on the immune system under a single severe incidence of stress and found that CM6271 is effective in enhancing the recovery of NK cell activity in mice after restraint loading for 18 h [15]. However, to develop a routine method of conditioning immune functions under stress encountered on a daily basis in society, it is more practical to use a model that presents relatively mild but repeated stress over a prolonged period of time than severe transient stress.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint Stress Loading. The mouse was placed in a 50 mL conical polyethylene tube with more than 30 air holes 5 mm in diameter and subjected to restraint stress for 18 h in the cage in the feeding room, as reported previously ( , ). While the test mice were restrained, the control mice were kept in the normal environment without access to food or water.…”
Section: Methodsmentioning
confidence: 99%
“…Stress can have detrimental effects on a variety of immune functions, including NK activity, and a marked decrease in NK activity was observed in mice that had been submitted to restraint stress for 12 or 18 hours (51). Oral administration of CM6271, described as a freeze-dried ''preparation'' from the mycelia of Tricholoma matsutake, for 10 days before the restraint period promoted the recovery of NK cell activity such that CM6271-treated mice showed almost normal NK activity on day 7, whereas water-treated controls exhibited depressed NK activity even on day 10.…”
Section: Pleurotus Ostreatusmentioning
confidence: 99%